Association of omega-3, omega-6 fatty acids intakes and omega-6: omega-3 ratio with the prevalence of suicidal ideation: mediating role of C-reactive protein - Hao Lin; Zhibin Bai; Daoke Wu; Qi Yang; Shuangshuang Qu (Lipids in Health and Disease)
Abstract Background Although dietary omega fatty acids have been recognized for positive effects on mental health, the specific association between omega fatty acids intake and suicidal ideation remains ambiguous. This study aims to explore the potential association between the prevalence of suicidal ideation and dietary omega fatty acids intake in American adults. Methods The data of 27,944 American adults collected from National Health and Nutrition Examination Survey (NHANES) were analyzed in this study. To assess the association between dietary omega fatty acids intake and suicidal ideation as measured by Item 9 of PHQ-9, logistic regression, restricted cubic spline regression, and stratified analyses, mediation analyses were employed. Results Logistic regression analyses indicate that the intakes of omega-3 and omega-6 fatty acids were inversely associated with the prevalence of suicidal ideation, and dietary omega-6/omega-3 ratio was positively associated with the prevalence of suicidal ideation. Subgroup analyses further revealed a stronger association between suicidal ideation and omega fatty acids intake in individuals with a history of stroke. Furthermore, a saturation effect and non-linear association were identified between omega-3 and omega-6 fatty acids intake and the prevalence of suicidal ideation, characterized by an L-shaped curve with an inflection point at 1.36 g/d, 13.69 g/d, respectively. Notably, C-reactive protein (CRP) partially mediated the association between omega-6, omega-3 fatty acids intake and suicidal ideation by a proportion of 3.8% and 4.0%. Conclusion The findings of this study suggest that higher omega-3 and omega-6 fatty acids intake and lower omega-6/omega-3 ratio is associated with a declined prevalence of suicidal ideation. Clinical trial number Not applicable.